PENGEMBANGAN LATIHAN SOAL TEMA LEBENSMITTELEINKAUF BERBASIS GAME ARCHERY ART UNTUK SISWA SMA KELAS XI SEMESTER II - Fatoni, Achmad Rizal; Wahyuningsih, Fahmi (LATERNE, 2023)
Reading is an activity when the writer makes a reading or text using a certain language so that it can be conveyed to the reader. Conventional delivery of material (recitation or lecture methods) makes students feel bored quickly and tends not to be involved in learning. The recitation method tends to be monotonous for students. In reading there is a skill, namely reading skills and efforts are needed to achieve learning goals. This effort can be carried out by educators by providing practice questions by utilizing a learning media technology, namely the Game Archery Art media which is operated using Microsoft PowerPoint Software. The use of easy and fun Archery Art Game media can improve the quality of students' understanding. The material taken for Media Game Archery Art is the Deutsch Ist Einfach 2 book which is intended for Highschool class XI Semester II. The theme used in the practice questions in this scientific article is Alltagsleben (everyday life) with the sub-theme, namely Lebensmitteleinkauf (shopping) and the form of the exercises used is in the form of multiple exercises including intrapersonal conversations and pictures of buying goods. The formulation of the problem in this scientific article is how to develop an exercise on the Lebensmitteleinkauf theme based on Game Archery Art for class XI high school students in semester II? This scientific article has the objective of describing the development of the Lebensmitteleinkauf themed practice exercises based on Game Archery Art for class XI senior high school students in semester II. A qualitative approach with the literature study method will be applied in this scientific article. The data source taken in this scientific article is the Deutsch Ist Einfach 2 book. The results of the aspects analyzed in this scientific article are descriptions of the development of practice questions that are relevant to the 2013 Curriculum, the development of practice questions that are relevant to Bloom's Taxonomy, and the development of exercises questions that are relevant to the Game Archery Art media.